The Effectiveness of Traditional the Method of Amputation and Treatment at the Lower Leg Level of Patients with Diabetic Foot Syndrome with Critical Lower Limb Ischemia - Rakhimov, Azizjon Yakhyoyevich (European Journal of Life Safety and Stability (2660-9630), 2022)
Aretrospective analysis of the medical records of 134 DM patients who underwent lower leg amputation was performed at the clinical base of the Bukhara State Medical Institute “Bukhara Multidisciplinary Regional Hospital” during62004 -2016. In this study, the patients included in the study underwent amputation of the lower leg according to Mitish-Svetukhin and studied the localization of the necrotic process, the duration of diabetes mellitus, the time of admission from the beginning of the pathological process, microbial contamination of the wound bed and intoxication indicators. Analysis of the obtained results revealed the following unsatisfactory results: postoperative wound suppuration in 16 (1,1. 9,9%) patients resulted in forced re-amputation of the lower leg in 5 (3,7%) cases, in one case high amputation was performed at the hip level. Four cases (3.0%) were fatal.